Stochastic models in reliability engineering - Cui, Lirong, 1960-; Frenkel, Ilia, 1950-; Lisnianski, Anatoly (CRC Press, 2020)
"This volume is a selected of papers on stochastic models in system reliability, which are presented in the Third International Symposium on Stochastic Models in Reliability Engineering, Life Sciences and Operations Management (SMRLO-2019) held in Beijing, China, from May 28-31, 2019. Methods presented in this book are real-world examples developed and demonstrating essential reliability and availability improvement for such industrial equipment as medical magnetic resonance inspection (MRI), power systems, traction drives for a search and rescue helicopter, and air conditioning systems. Presented real case studies include the redundant multi-state air conditioning systems for chemical laboratories, covers assessments of reliability and fault tolerance and availability calculations. Discusses conventional and contemporary topics in reliability engineering and includes degradation, networks and dynamic reliability, resilience and multi-state systems which are the relatively new topics to the field. Targeted to engineers and scientists, graduate and postgraduate students involved in reliability design, analysis and experiments and applied probability and statistics"--